Acridine: A Scaffold for the Development of Drugs for Alzheimer's Disease - Sharma, Anuradha; Piplani, Poonam (Current Topics in Medicinal Chemistry, 2023)
Alzheimer's disease (AD) is drawing scientists' consideration, being one of the gravest diseases mankind will have to battle against in the near future. The number of people with AD is expected to triple in the next 40 years. It is a most common age-related multifactorial neurodegenerative disease and characterized by two histopathological hallmarks; the formation of senile plaques composed of the amyloid-β (Aβ) peptide and neurofibrillary tangles composed of hyperphosphorylated tau protein. Discovery and development of rationally designed multi-targeted ligands for the management of AD could be more beneficial than classical single targeted molecules. Acridine, a heterocyclic nucleus is a sole moiety in various existing drug molecules such as quinacrine (antimalarial), acriflavine and proflavine (antiseptics), ethacridine (abortifacient), amsacrine and nitracine (anticancer) and tacrine (anti-Alzheimer). It is proposed that acridine may combat the AD by acting on several targets like acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), dual specificity tyrosine kinase 1A (Dyrk 1A), amyloid and prion protein (PrPC) etc. involved in its pathogenesis. The main aim of this compilation is to review the most promising therapeutic developments within the vast research area dealing with acridine derivatives. Further research is required to evaluate the effectiveness of the acridine derivatives with various substitutions in the treatment of AD. In conclusion, our review will suggest the potentiality of the versatile acridine framework for drug designing and developing novel multi-target inhibitors for the Alzheimer’s disease.
Keywords: Drug designing